The Australian Traumatic Brain Injury National Data (ATBIND) project: a mixed methods study protocol. Issue 7 (3rd August 2022) - O'Reilly, Gerard M; Curtis, Kate; Kim, Yesul; Mitra, Biswadev; Hunter, Kate; Ryder, Courtney; Hendrie, Delia V; Rushworth, Nick; Afroz, Afsana; D'Angelo, Shane; Tee, Jin; Fitzgerald, Mark C
Abstract: Background: Traumatic brain injury (TBI) is the largest contributor to death and disability in people who have experienced physical trauma. There are no national data on outcomes for people with moderate to severe TBI in Australia. Objectives: To determine the incidence and key determinants of outcomes for patients with moderate to severe TBI, both for Australia and for selected population subgroups, including Aboriginal and Torres Strait Islander Australians. Methods and analysis: The Australian Traumatic Brain Injury National Data (ATBIND) project will analyse Australia New Zealand Trauma Registry (ATR) data and National Coronial Information Service (NCIS) deaths data. The ATR documents the demographic characteristics, injury event description and severity, processes of care, and outcomes for people with major injury, including TBI, assessed and managed at the 27 major trauma services in Australia. We will include data for people with moderate to severe TBI (Abbreviated Injury Scale [AIS] (head) score higher than 2) who had Injury Severity Scores [ISS] higher than 12 or who died in hospital. People will also be included if they died before reaching a major trauma service and the coronial report details were consistent with moderate to severe TBI. The primary research outcome will be survival to discharge. Secondary outcomes will be hospital discharge destination, hospital length of stay, ventilator‐free days, and health service cost. Ethics approval: The Alfred Ethics Committee approved ATR data extraction (project reference number 670/21). Further ethics approval has been sought from the NCIS and multiple Aboriginal health research ethics committees. The ATBIND project will conform with Indigenous data sovereignty principles. Dissemination of results: Our findings will be disseminated by project partners with the aim of informing improvements in equitable system‐level care for all people in Australia with moderate to severe TBI. Study registration: Not applicable.